Perfil imunofenotípico e nível de citocinas plásmáticas em portadores de hepatite C crônica com diferentes graus de comprometimento hepático - Magnoni, Mariana Sartori [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The chronic hepatitis C virus (HCV) is the cause of chronic liver disease affecting about 3% of world population, approximately 170 million people. Investigations of the immune response in individuals infected with HCV is justifiable because this form infectious disease whose immunological changes are directly related to the development and maintenance of infection. This project aimed to evaluate aspects that make up the immune chronic hepatitis C patients with different degrees of liver damage response. The study included patients HCV+ (n = 83), genotype 1, pretreatment, which were classified according to the rate of hepatic fibrosis determined by biopsy (METAVIR classification), composed of: G1 (n = 15) patients in stages F0 (no fibrosis) + F1 (fibrosis expansion of port spaces), G2 (n = 21) patients in the F2 stage (few sources of fibrosis in portal ), G3 ( n = 15 ) patients with stage F3 (early nodule formation), G4 (n = 32) patients with stage F4 (severe fibrosis), G5 (n = 16) volunteer blood donors (control group). Immunophenotypic characteristics of subpopulations of peripheral blood leukocytes (total NK cells, NKdim , NKbright , myeloid dendritic cells and plasmacytoid , classical monocytes, pro- inflammatory CD4 + / CD8 + cells), cytokine levels and plasma chemokines (were evaluated TGF- β , TNF - α , CCL2 , CCL3 , CCL4 , CCL5 , CXCL8 , CXCL9, CXCL10), analyzing their relationship with the progression of fibrosis. All frequencies of evaluated leukocyte subpopulations are altered in patients with chronic hepatitis C compared with healthy subjects. In addition, no correlation between the degree of fibrosis and the amount of CD4, CD8, pro-inflammatory monocytes and circulating NKbright cells. Increased levels of TNF-α were observed in cirrhotic patients (G4) and TGF - β in HCV + groups with moderate hepatic fibrosis (G2 and G3). Plasma chemokine CXCL9/MIG, CXCL10/IP-10, CXCL8/IL-8, CCL2/MPC-1, ...

O vírus da hepatite C crônica (VHC) é causa de doença hepática crônica afetando cerca de 3% da população mundial, aproximadamente 170 milhões de pessoas. Investigações sobre a resposta imune em indivíduos infectados com HCV é justificável pelo fato desta constituir doença infecciosa cujas alterações imunológicas têm relação direta com o desenvolvimento e a manutenção da infecção. Este projeto visou avaliar aspectos que compõem a resposta imune de pacientes com hepatite C crônica com diferentes graus de lesão hepática. Foram incluídos no estudo pacientes VHC+ (n=83), genótipo 1, pré-tratamento, os quais foram estratificados conforme o grau de fibrose hepática determinada por biópsia (classificação METAVIR), compondo: G1 (n = 15) pacientes nos estágios F0 (nenhuma fibrose) + F1 (fibrose em expansão dos espaços porta); G2 (n = 21) pacientes no estágio F2 (poucas fontes de fibrose nos espaços porta); G3 (n = 15) pacientes em estágio F3 (início da formação de nódulos); G4 (n = 32) pacientes em estágio F4 (fibrose severa); G5 (n = 16) doadores de sangue voluntários (grupo controle). Foram avaliadas características imunofenotípicas de subpopulações de leucócitos do sangue periférico (células NK totais, NKdim, NKbright, células dendríticas mielóides e plasmocitóides, monócitos clássicos e pro-inflamatórios, linfócitos T CD4+/CD8+), níveis de citocinas e quimiocinas plasmáticas (TGF-β, TNF-α, CCL2, CCL3, CCL4, CCL5, CXCL8, CXCL9, CXCL10), analisando a relação destes com a progressão da fibrose. Todas as frequências das subpopulações leucocitárias avaliadas estão alteradas em portadores de hepatite C crônica comparados com indivíduos saudáveis. Além disso, há correlação entre o grau de fibrose e a quantidade de linfócitos T CD4, T CD8, monócitos pro-inflamatórios e células NKbright circulantes. Níveis aumentados de TNF-α foram observados ...
Keywords: Hepatite C; Citocinas; Marcadores biologicos; Figado - Doenças; Fibromialgia; Liver Diseases